Allocating Unique Property Reference Numbers (UPRNs) to general practitionerrecorded patient addresses using a deterministic address-matching algorithm: evaluation of representativeness and bias in an ethnically-diverse inner city population. (22nd November 2019) - Harper, Gill; Stables, David; Boomla, Kambiz; Robson, John; Fry, Richard; Ahmed, Zaheer; Dezateux, Carol
No abstract available